Depositional environment of the Sarmord Formation (Valanginian-Aptian) in selected areas, northeastern Iraq - Saleh, Safaa A.; Tamar-Agha, Mazin Y.; Balaky, Sardar M. (Iraqi Journal of Science, 2023)
The current study deals with microfacies and the depositional environment of the Lower Cretaceous Sarmord Formation at selected sections in Sulaimani and Erbil Governorates, northern Iraq. The Sarmord Formation alternates rhythmically between yellowish grey marly limestones and grey black marls. These lithologies are observed in all studied sections of Sarmord Formation in northern Iraq. Petrographic investigation of this study based on 240 thin sections demonstrated that the carbonate constituents are mainly composed of skeletal and non-skeletal grains. The skeletal grains include a variety of foraminiferas (planktonic and benthonic), bioclasts, calcispheres, ostracods, radiolaria, echinoderms, sponge spicules, ammonoids and belemnites. The non-skeletal grains consist of rare intraclasts. Based on field observations, two major lithofacies are recognized in the studied sections, namely marly limestone and marl lithofacies. Depending on the detailed microfacies analysis, two main microfacies, which in turn are divided into four sub-microfacies, were identified. These facies were subdivided upon their environmental interpretation into two types of facies associations: deep shelf and basinal. From the results of petrographic, facies, and textural analyses, it is concluded that Sarmord Formation in the studied sections was deposited at a rimmed carbonate platform. With a gradual shallowing of the basin from basinal sediments at the lower part overlying by deep shelf sediments in the uppermost part of the formation in the studied sections.